Supporting creativity: With emergent shapes in shape grammars - Reis, J. (2023)
This paper describes a computational infrastructure used to support creative design in detecting emergent shapes in the specific context of shape grammar implementation. Shape grammars have been used to represent the knowledge behind the creative work of architects, designers and artists. This kind of grammars are inherently visual and they allow the implementation of computational mechanisms to either synthesize or analyze designs of visual languages, including the detection of emergent sub-shapes languages. They have obvious applications to design, including for marketing. The infrastructure presented, together with the algorithm to which it gives support, the latter proposed in another, twin, paper, is a core component of a system, described in our past work, that allows users to build their own shape grammars and experiment with and use them.